Transmembrane protein DCBLD2 is correlated with poor prognosis and affects phenotype by regulating epithelial-mesenchymal transition in human glioblastoma cells. Issue 6 (7th April 2021) - Cheng, Shuai; Wang, Liang-Yan; Wang, Chuan-Hui; Wang, Fa-Kai; Zhu, Bing; Zhang, Peng; Wang, Guo-Hua
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: We attempt to investigate the biological function of the discoidin, complement C1r/C1s, Uegf, and Bmp1 and Limulus factor C, Coch, and Lgl domain-containing 2 (DCBLD2) in glioblastoma, as well as its effect on the epithelial-mesenchymal transition (EMT) process. Methods: The public expression data of glioblastoma samples and normal brain samples from The Cancer Genome Atlas database, Genotype-Tissue Expression database and Chinese Glioma Genome Atlas database were used to analyze the expression of DCBLD2 and its relationship with the survival of patients with glioblastoma. Quantitative real-time PCR and western blot were used to evaluate mRNA and protein levels of DCBLD2. Cell viabilities were tested using Cell Counting Kit-8 and clone formation assays. Cell invasive and migratory abilities were measured by transwell assays. Results: DCBLD2 expression was upregulated in glioblastoma and has a significantly positive correlation with the WHO classification. In addition, high expression of DCBLD2 was closely correlated with poor prognosis in primary and recurrent patients with glioblastoma. What is more, we found that knockdown of DCBLD2 notably reduced the cell proliferative, invasive and migratory capacities by elevating the expression of E-cadherin and inhibiting the expression of vimentin, snail, slug and twist. However, overexpression of DCBLD2 presented the opposite results. Conclusion: The current study reveals that high expression of DCBLD2 is closely related to poor prognosis in glioblastoma and can significantly enhance the tumor cell viability and metastasis by activating the EMT process, suggesting that DCBLD2 may be a possible biomarker for glioblastoma treatment.